2002
DOI: 10.4319/lo.2002.47.2.0558
|View full text |Cite
|
Sign up to set email alerts
|

Primary production, respiration, and calcification of a coral reef mesocosm under increased CO2 partial pressure

Abstract: The effect of increased CO2 partial pressure (pCO2) on the community metabolism (primary production, respiration, and calcification) of a coral community was investigated over periods ranging from 9 to 30 d. The community was set up in an open‐top mesocosm within which pCO2 was manipulated (411, 647, and 918 µatm). The effect of increased pCO2 on the rate of calcification of the sand area of the mesocosm was also investigated. The net community primary production (NCP) did not change significantly with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 20 publications
9
108
1
2
Order By: Relevance
“…High rates of dissolution of high-Mg calcite have also been measured on natural reefs (Great Barrier Reef algal ridges, Chisholm [2000]; Hawaiian reef sediments, Halley and Yates [2000]), and in reef flat sediments [Boucher et al, 1998]. Leclercq et al [2002] found that sediment dissolution in their mesocosm experiments did not vary with pCO 2 variations between 411 and 918 µatm, although it is not clear whether the mesocosm sediments included high-Mg calcite.…”
Section: Natural Variability Of the Carbonate System On Coral Reefsmentioning
confidence: 99%
“…High rates of dissolution of high-Mg calcite have also been measured on natural reefs (Great Barrier Reef algal ridges, Chisholm [2000]; Hawaiian reef sediments, Halley and Yates [2000]), and in reef flat sediments [Boucher et al, 1998]. Leclercq et al [2002] found that sediment dissolution in their mesocosm experiments did not vary with pCO 2 variations between 411 and 918 µatm, although it is not clear whether the mesocosm sediments included high-Mg calcite.…”
Section: Natural Variability Of the Carbonate System On Coral Reefsmentioning
confidence: 99%
“…Models forecast that with increasing atmospheric CO 2 , seawater pH may decrease by 0.3-0.4 units by 2100 (Haugan and Drange, 1996;Brewer, 1997;Caldeira and Wickett, 2005). Under such a scenario, experimental data suggest an alarming 11-40% decline in the calcification of reef building organisms (Gattuso et al, 1998, Langdon et al, 2000Marubini et al, 2001;Leclercq et al, 2002;Reynaud et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Yet there may be winners and losers among individual species with different responses to declining pH, resulting in not only biodiversity declines (Fabricius et al 2011) but likely also hard-topredict changes in species interactions (Kroeker et al 2011). Laboratory studies demonstrate that coral calcification rates for certain species may decrease as much as 20-54% at atmospheric P CO 2 levels of 56.7 Pa (or 560 matm; Leclercq et al 2002;Langdon et al 2003), but some models predict even more drastic decline of up to 85% (Kleypas and Langdon 2006).…”
mentioning
confidence: 99%